1988
DOI: 10.1136/thx.43.4.300
|View full text |Cite
|
Sign up to set email alerts
|

Dose related effects of salbutamol and ipratropium bromide on airway calibre and reactivity in subjects with asthma.

Abstract: The relationship between change in airway calibre and change in airway reactivity after administration of bronchodilator drugs has been investigated by comparing the effect of increasing doses ofinhaled salbutamol and ipratropium bromide on the forced expiratory volume in one second (FEV,), specific airways conductance (sGaw), and the dose of histamine causing a 20% fall in FEV, (PD20) in six subjects with mild asthma. On each of 10 occasions measurements were made of baseline FEV,, sGaw, and PD20 after 15 min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
27
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(38 citation statements)
references
References 40 publications
10
27
1
Order By: Relevance
“…Several studies have evaluated the protection of beta 2 -adrenoceptor agents against different bronchoconstrictive challenges. Whilst a dose-response effect has been demonstrated for chemical stimuli [17,[25][26][27], contradictory results have been obtained with exercise [28,29]. In the present study, 25 and 50 µg doses of salmeterol provided the same protection against EIA at 1 h. After 12 h, although no statistical difference emerged between the two dosages in the mean of the percentage drops in FEV1, only SLM 50 was more protective than placebo.…”
Section: Discussioncontrasting
confidence: 33%
“…Several studies have evaluated the protection of beta 2 -adrenoceptor agents against different bronchoconstrictive challenges. Whilst a dose-response effect has been demonstrated for chemical stimuli [17,[25][26][27], contradictory results have been obtained with exercise [28,29]. In the present study, 25 and 50 µg doses of salmeterol provided the same protection against EIA at 1 h. After 12 h, although no statistical difference emerged between the two dosages in the mean of the percentage drops in FEV1, only SLM 50 was more protective than placebo.…”
Section: Discussioncontrasting
confidence: 33%
“…A larger concentration of a β 2 -agonist may be required to prevent contraction to a potent stimulus as a provocation test, as compared with the concentration of the drug to produce relaxation of the relatively modest level of bronchospasm at baseline [31]. Several studies showed a relationship between bronchodilator dose and the degree of inhibition of provocation [32]. A greater concentration of salmeterol may be required to prevent contraction to UNDW provocation than is required to produce relaxation.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that 'functional antagonism' might not simply be the mechanism by which bronchodilators exert a pre-protective effect. It has been proposed (Persson et al, 1982), that &2-agonists, for example, have effects on cells other than airway smooth muscle and that this may contribute to their protective effects in human asthmatic subjects (Britton et al, 1988).…”
Section: Discussionmentioning
confidence: 99%